Assessment of Aerobic and Respiratory Growth in the Lactobacillus casei Group - Zotta, Teresa (Public Library of Science, 2014)
One hundred eighty four strains belonging to the species Lactobacillus casei, L. paracasei and L. rhamnosus were screened for their ability to grow under aerobic conditions, in media containing heme and menaquinone and/or compounds generating reactive oxygen species (ROS), in order to identify respiratory and oxygen-tolerant phenotypes. Most strains were able to cope with aerobic conditions and for many strains aerobic growth and heme or heme/menaquinone supplementation increased biomass production compared to anaerobic cultivation. Only four L. casei strains showed a catalase-like activity under anaerobic, aerobic and respiratory conditions and were able to survive in presence of H(2)O(2) (1 mM). Almost all L. casei and L. paracasei strains tolerated menadione (0.2 mM) and most tolerated pyrogallol (50 mM), while L. rhamnosus was usually resistant only to the latter compound. This is the first study in which an extensive screening of oxygen and oxidative stress tolerance of members of the L. casei group has been carried out. Results allowed the selection of strains showing the typical traits of aerobic and respiratory metabolism (increased pH and biomass under aerobic or respiratory conditions) and unique oxidative stress response properties. Aerobic growth and respiration may confer technological and physiological advantages in the L. casei group and oxygen-tolerant phenotypes could be exploited in several food industry applications.